Clinical Supervision on the Professional Development of Teachers - Macabuhay, Henry (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the impact of clinical supervision on the professional development of teachers in Emilio Lee Llacer Sr. High School, San Jacinto District, Masbate, during School Year 2024–2025. It was anchored on Adult Learning Theory, Reflective Practice Theory, and Clinical Supervision Theory, with the view that clinical supervision is a formative, collaborative, and non-evaluative process that supports teacher growth through observation, feedback, and reflection. The study used a descriptive quantitative research design and employed a researcher-made questionnaire validated by experts and pilot-tested for reliability. Using purposive sampling, 15 public secondary school teachers who had experienced at least one cycle of clinical supervision were selected as respondents. Data were gathered through a structured survey and analyzed using frequency count, rank, percentage, weighted mean, and Pearson correlation. Findings showed that teachers experienced notable challenges in the implementation of clinical supervision, particularly limited time for meaningful feedback, lack of follow-up support, inconsistent practice, and unclear expectations. Despite these concerns, teachers agreed that clinical supervision positively affected their professional development, especially in constructive feedback, instructional planning, classroom management, teaching confidence, student engagement, and reflective practice. They also strongly perceived clinical supervision as highly effective in enhancing instructional skills, promoting collaboration, and improving classroom practices. The study concluded that clinical supervision remains a highly valued and effective developmental tool despite implementation issues. It recommends strengthening structured feedback and follow-up, improving supervisor training, and ensuring consistency and clarity in supervision procedures. This study aligns with SDG 4: Quality Education by supporting teacher quality and continuous professional development. Its sustainability impact lies in strengthening educational and institutional sustainability through improved instructional practice, reflective teaching, and supportive supervisory systems.